Medium Access in Spread-Spectrum Ad Hoc Networks with Multiuser Detection. (4th August 2008) - Kusume, Katsutoshi; Vilzmann, Robert; Müller, Andreas; Hartmann, Christian; Bauch, Gerhard
Abstract : Conventional medium access control protocols are designed to avoid simultaneous transmissions, based on a simple collision model in the underlying physical layer. Recently, strong physical layer capabilities, enabled by multiuser detection techniques, have been studied in connection with simple medium access control protocols, for example, slotted ALOHA. We think that neither of these extreme approaches is optimum, particularly in general scenarios where network nodes with different signal processing capabilities coexist. Instead of dealing with interferences in either of the two layers alone, both medium access control and physical layer functionalities should be designed to cooperate and complement each other. We discuss several key aspects for designing such a protocol, especially with an emphasis on iterative multiuser detection, which can provide a good tradeoff between performance and complexity. We propose a new protocol called MUD-MAC which satisfies these key aspects. We analyze its throughput bound and also perform numerical simulations. The simulation results show excellent throughput improvements. It is also demonstrated that the MUD-MAC protocol provides certain fairness among network nodes with different signal processing capabilities.